2013
DOI: 10.1113/jphysiol.2013.258061
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol blunts the positive effects of exercise training on cardiovascular health in aged men

Abstract: Key points• In rodents, resveratrol has been shown to enhance training-induced changes in cardiovascular function, exercise performance and the retardation of atherosclerosis. We examined the effect of 8 weeks of exercise training with and without concomitant resveratrol supplementation in aged men.• Exercise training potently improved blood pressure, blood cholesterol, maximal oxygen uptake and the plasma lipid profile.• Resveratrol supplementation reduced the positive effect of exercise training on blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
254
6
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(277 citation statements)
references
References 96 publications
15
254
6
2
Order By: Relevance
“…Whilst the data from Timmers et al (2011) was encouraging, recently Scribbans and colleagues (2014) reported that resveratrol supplementation during exercise training in healthy individuals can result in a maladaptive response in exercise-stimulated gene expression [176]. In agreement with this observation, Gliemann et al (2013) showed that resveratrol supplementation in combination with high-intensity training in older men not only blunted the increase in maximal oxygen uptake observed in the placebo group, but also eradicated the effects of the exercise to reduce low-density lipoprotein, total cholesterol and triglyceride concentrations in the blood [177]. Using a similar protocol, Olesen et al…”
Section: Nicotinamide Riboside (Nr)mentioning
confidence: 93%
“…Whilst the data from Timmers et al (2011) was encouraging, recently Scribbans and colleagues (2014) reported that resveratrol supplementation during exercise training in healthy individuals can result in a maladaptive response in exercise-stimulated gene expression [176]. In agreement with this observation, Gliemann et al (2013) showed that resveratrol supplementation in combination with high-intensity training in older men not only blunted the increase in maximal oxygen uptake observed in the placebo group, but also eradicated the effects of the exercise to reduce low-density lipoprotein, total cholesterol and triglyceride concentrations in the blood [177]. Using a similar protocol, Olesen et al…”
Section: Nicotinamide Riboside (Nr)mentioning
confidence: 93%
“…It has been shown resveratrol enhanced the beneficial effects of exercise on cardiac function in normal young rats [26]. However, the complementary effect was not supported by a recently reported clinical study in which resveratrol blunted the cardiovascular protective effect in elderly men [27]. Thus further studies using experimental animal model and in clinical setting to assess the potential synergy between exercise and resveratrol are needed to support its potential role in complementary medicine.…”
Section: Introductionmentioning
confidence: 87%
“…Recent studies in humans, by contrast, suggest that in aged, but healthy individuals RV blunts the positive cardiovascular effects of physical exercise (Gliemann et al, 2014(Gliemann et al, , 2013Olesen et al, 2014b). When submitted to eight weeks of high intensity training and a daily intake of either 250 mg of RV or placebo, the subjects that received RV showed no increase in the capillary-to-fiber ratio or the concentration of vascular endothelial growth factor in the vastus lateralis.…”
Section: Accepted M Manuscriptmentioning
confidence: 95%
“…On the other hand, enough evidence has been gathered to suggest that compromised populations such as the elderly do benefit from treatment with RV (Smoliga et al, 2013). Even though a recent series of publications in aged humans (Gliemann et al, 2014(Gliemann et al, , 2013Olesen et al, 2014b) reveals no benefit from RV supplementation in a broad range of cardiovascular and metabolic parameters, further research needs to be conducted to definitely validate the claims both in favor and against RV.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation